Smart and sustainable transport: short review of the special issue - Gopalakrishnan, Kasthurirangan; Chitturi, Madhav V.; Prentkovskis, Olegas (Transport, 2015)
„Smart and sustainable transport: short review of the special issue" Transport, 30(3), p. 243-246 First published online: 2 September 2015